IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING DI SMA NEGERI 8 PEKANBARU - Hayatun Nupus; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Program of Guidance and Counseling is designed to respond various problems that counselor facing in the school. But in reality, in the implementation of the program there are usually obstracles such as discrepancy between the arranged program and the implementation on the field, lack of time allocation, proffesional Guidance and Counseling staff, and facilities and infrastructure that are inadequate for the implementation of the program. The purpose of this research is to find out what kind of type and content of the program of Guidance and Counseling and how the implementation of the program of Guidance and Counseling at School. This research uses quanlitative research method, a descriptive research method wich is tend to uses analysis, in this case all collected data processed non-statistically to describe the result of the research. Subject in this research is a Guidance and Counseling teacher. The research data collected by open-ended questionnaire and interview. From the results of research can be conclude that the type of arranged program is yearly program, monthly program, semester program and annual program. The content of the program are in the form of four types of services such as basic service, responsive service, specialization service and individual planning and system suport. The implementation of program is according to the planned program, but there are still some programs that have not been done well because of obstacles in the implementationKeyword: Guidance and Counseling Program, Implementation